1,2-Diaminoethane-containing epoxy resins for separation of aldehydes - Biçak, Niyazi; Soydan, A.Bahattin; Şenkal, B.Filiz; Koza, Güneş; Yener, Mine (Elsevier BV, 1999)
Abstract Epoxy-amine resin obtained by inverse suspension polycondensation of epichlorohydrin with ethylenediamine has been demonstrated to be very useful for selective separation of aldehydes from the mixtures. 1,2-Diamino ethane units in the crosslinked structure can be regard as polymeric analog of Wanzlick reagent (1,2-dianilo ethane) which readily condenses with aldehydes to form five-membered cyclic structures, imidazolines. In the presence of mineral acids the imidazoline ring decomposes into its components. This reverse reaction serves a means of regenerability of the aldehyde loaded polymer. The method described in the present study is especially suitable for extraction and recovery of aromatic aldehydes from organic mixtures, even in small quantities. The method works also for aliphatic aldehydes. However, in that case, aldol condensation products form in the solution and the insoluble polymer sorbs these by-products together with the aldehyde itself. Aldehyde sorptions are rapid in water-miscible solvents such as dioxane and methanol. Whereas in cyclohexane aldehyde sorption is very slow, due to hydrophilicity of the polymer.